Repair Initiations Analysis in the Classroom Interaction - Yohanis Nurak Siwa; Maria Goreti Djehatu (Soshum: Jurnal Sosial dan Humaniora, 2018)
The study was carried out to identify kinds of repair initiations, i.e. the indication which shows that there is a trouble that has to be repaired, that occur in conversation. The data were taken from an English teacher and the eleventh grade students of a vocational high school. Subjects of the study were an English teacher and 20 students. In obtaining the data, class discussion was about language-learning task has been prepared by the teacher. The device used by the researcher was a handy-camera to record and capture the discussion in classroom discourse. The result of the study showed that the English teacher was able to use several types of repair initiations in the classroom interaction. It involved unspecified repairs, repeats or partial repeats, and request for translation or information. In addition, the students were able to play their roles in the classroom by initiating two types of repair initiations; they are included unspecified repair, and (partial) repeat. Moreover, the frequency of occurrence of repair initiation types done by the teacher was the request for translation or information repair initiation mostly occured on the teacher’s turn, while on the second place the teacher frequently used repeats or partial repeats on his turn. By initiating repairs, the researcher also decided the kinds of repair initiation that frequently occurred on the students’ turn. Unspecified repair was mostly used by the students in the classroom interaction, whereas repeats or partial repeat were less frequently used on the students’ turn.